An Exploration of the Image Processing Techniques for the Detection of Leukemia - Premnath, A.; Meenakshi Selvi, V. S. (Asian Journal of Engineering and Applied Technology, 2018)
In the pathological diagnostic method, categorization of blood cell has more essential to detect and analyze the disease. The complications that are connected with blood can be distributed only after the blood cell classification. The illness that begins with the bone marrow is the Leukemia. Therefore, it must be handled at the beginning step and proceeds to death if continuing untreated. This present research elucidates an investigation of diagnosing leukemia from microscopic blood image exhausting various image processing algorithms.